DIFFERENCES OF TOLERANCE CHARACTER PLANTING STRATEGIES RELIGIOUS INTEREST STUDENTS IN SDN INPRES 6.88 PERUMNAS 2 KOTA JAYAPURA - Rofiki, A. Arif; Amin, Muliaty; Susdiyanto, Susdiyanto; Yusuf T, Muh. (Jurnal Diskursus Islam, 2020)
This paper discusses the various strategies for cultivating the character of inter-religious tolerance in students of SDN Inpres 6.88 Perumnas 2 Kota Jayapura which is carried out through 1) school policies; 2) habituation to differences; 3) habituation to equations, and 4) group heterogeneity exercises. This research is field research. The research approach used in this research includes methodological (phenomenological) and scientific approaches (normative, juridical, and pedagogical theological approaches). The research method used was an interview, observation, and documentation. The results of this study indicate that the character of interreligious tolerance in students of SDN Inpres 6.88 Perumnas 2 Kota Jayapura is carried out through several strategies, namely: First, school policy. A strong commitment must be possessed by school policymakers in cultivating the character of tolerance between religious believers in students. This commitment is manifested in the inclusion of the character values of tolerance among religious believers in the mission, goals, and school regulations. Second, habituation to differences. The teacher accustoms students to differences from an early age. This is done by giving understanding to students to appreciate the differences that exist between them. Besides, in learning the teacher also trains students to appreciate differences of opinion when discussing. Third, habituation to equality. The teacher gives the understanding that all students have the same position in a school that is, both become students who have the same rights and obligations. Students when learning are accustomed to the teacher to see the similarities in meaning if there are different answers. . The teacher invites students to think from the same point of view, not from each student. Fourth, exercise heterogeneity in groups. The teacher gives group heterogeneity exercises to students in assigned group discussions during learning. The learning strategy used by the teacher in group discussion assignments is the cooperative learning strategy. Students work together in their study groups to complete the assignments the teacher has given them. Heterogeneity of study groups that favor cooperation can train and accustom students to learn to respect and tolerate differences that exist between themselves and their peers in terms of ethnicity, religion, social strata, or abilities.